Multimodal approach to the management of pregnant women with brain arteriovenous malformation - S.B. Kerchelaeva; V.V. Dergunova; N.Yu. Ivannikov; O.Yu.Yushina (LCC «Medicine-Inform», 2022)
S.B. Kerchelaeva1, V.V. Dergunova1, N.Yu. Ivannikov2, O.Yu.Yushina2 1Pirogov Russian National Research Medical University, Moscow, Russian Federation 2F.I. Inozemtsev City Clinical Hospital, Moscow, Russian Federation Extragenital diseases currently hold one of the leading positions among the causes of maternal death. Brain arteriovenous malformation (AVM) is a congenital anomaly of the vascular system, which is a pathological direct connection between small arteries and small veins without an interim capillary network. This phenomenon is a prerequisite for vessel rupture and hemorrhage that is potentially lethal or results in severe disability. Brain AVMs cause intracranial hemorrhages in 23% of pregnant women and maternal death in 5-12%. The authors share their experience with brain AVM in a pregnant woman with favorable maternal and fetal outcomes. Management approaches are discussed. Timely diagnosis of AVM during pregnancy, multimodal management approach to pregnancy, delivery, and postnatal period, and the development of medical care algorithm reduce the rate of maternal death and morbidity and improve perinatal outcomes. Keywords: pregnancy, delivery, postnatal period, arteriovenous malformation, hemorrhage, multimodal approach. For citation: Kerchelaeva S.B., Dergunova V.V., Ivannikov N.Yu., Yushina O.Yu. Multimodal approach to the management of pregnant women with brain arteriovenous malformation. Russian Journal of Woman and Child Health. 2022;5(2):153-156 (in Russ.). DOI: 10.32364/2618-8430-2022-5-2-153-156.